Genotypic Variability in Carbon Isotope Discrimination and Water Use Efficiency among Recombinant Inbred Lines of Sunflower (Helianthus annuus L.) - Afifuddin Latif Adiredjo; Philippe Grieu (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2018)
To evaluate genotypic variability in carbon isotope discrimination or CID and water use efficiency or WUE, recombinant inbred lines (RILs) population of sunflower (Helianthus annuus L.) was used. Seventy eight sunflower RILs were grown in greenhouse and 100 sunflower RILs were grown under field condition, and measured some morphological and physiological traits including leaf area at flowering (LAf), net CO2 assimilation rate (A) and transpiration per day at flowering (Ef). WUE, called “potential” WUE (WUEp), was calculated as the ratio of assimilation potential (Ap) to transpiration per day at flowering (Ef) where Ap was derived from the multiplication of A with LAf. The CID was significantly varied among RILs and there was significant negative genetic correlation between CID and WUEp. Heritability of the CID was higher rather than the WUEp which reflected wide genetic variability of CID. The genetic correlation between CID and WUEp and the wide genotypic variability of CID indicated that CID can be proposed as an indicator to determine WUE in sunflower and open a way in understanding the genetic diversity of the RILs which could be used as a basic consideration before applying selection program in sunflower breeding.